An experimentally validated couch and MLC tracking simulator used to investigate hybrid couch‐MLC tracking. Issue 3 (17th March 2017) - Toftegaard, Jakob; Hansen, Rune; Ravkilde, Thomas; Macek, Kristijan; Poulsen, Per Rugaard
Abstract : Purpose/objective: Couch and MLC tracking are two novel techniques to mitigate intrafractional tumor motion on a conventional linear accelerator, but both techniques still have residual dosimetric errors. Here, we first propose and experimentally validate a software tool to simulate couch and MLC tracking, and then use the simulator to study hybrid couch‐MLC tracking for improved tracking performance. Materials and methods: The tracking simulator requires a treatment plan and a motion trajectory as input and simulates the delivered monitor units and motion of all accelerator parts as function of time. The simulator outputs accelerator log files synchronized with the target motion as well as the MLC exposure error, which is a simple dose error surrogate. A series of couch and MLC tracking experiments were used to determine appropriate parameters for the simulator dynamics and to validate the simulator by its ability to reproduce the experimental tracking accuracy. Three hybrid couch‐MLC tracking strategies were investigated. All strategies divided the target motion in beam's eye view into motion perpendicular and parallel to the MLC leaves. In the hybrid strategies, couch tracking compensated for the following target motion components (in order of decreasing couch tracking contribution): (a) all perpendicular motion, (b) residual perpendicular motion less than half a leaf width, and (c) persistent residual perpendicular motion that was stable at a time scale of 1s. MLC tracking compensated for the remaining target motion. All tracking strategies were simulated with two prostate and two lung cancer single‐arc VMAT plans using 695 prostate trajectories and 160 lung tumor trajectories. The tracking error was quantified as the MLC exposure error. The couch motion was quantified as the mean speed, acceleration, and jerk of the couch. Results: The simulator reproduced the experimental gantry position with a mean (maximum) root‐mean‐square (rms) error of 0.07°(0.2°). The geometrical rms tracking error was reproduced with mean (maximum) absolute errors of 0.20 mm(0.23 mm) and 0.1 mm(0.23 mm) for MLC tracking parallel and perpendicular to the MLC leaves, and 0.40 mm(0.46 mm), 0.09 mm(0.25 mm), and 0.20 mm(0.46 mm) for couch tracking in the left‐right, anterior‐posterior, and cranio‐caudal directions. The MLC exposure error of VMAT MLC tracking was reproduced with a mean absolute error of 5.6%. All hybrid tracking strategies reduced the couch motion relative to pure couch tracking and improved the tracking accuracy compared with pure MLC tracking. The mean MLC exposure error reduction relative to no tracking was 66.6% (couch tracking), 72.9% (hybrid (1)), 70.2% (2), 59.1% (3), and 55.6% (MLC tracking) for lung tumor motion and 76.5% (couch tracking), 76.1% (1), 74.3% (2), 72.3% (3), and 35.9% (MLC tracking) for prostate motion. For prostate motion, pure MLC tracking resulted in rather large MLC exposure errors that were more than halved with all hybrid tracking strategies. Conclusion: A couch and MLC tracking simulator was developed and experimentally validated against a series of tracking experiments. All hybrid couch‐MLC tracking strategies improved MLC tracking. Two strategies also improved couch tracking of lung tumors. In particular, MLC tracking of prostate may be greatly improved by a modest degree of couch motion.